2008
DOI: 10.1681/asn.2006090983
|View full text |Cite
|
Sign up to set email alerts
|

Bmp in Podocytes Is Essential for Normal Glomerular Capillary Formation

Abstract: Bone morphogenetic protein (BMP) 4 exerts multiple biological effects on kidney and ureter development. To examine the role of BMP4 in glomerular morphogenesis, we generated transgenic mice with altered BMP4 function in podocytes by conferring tissue-specificity with the nephrin (Nphs1) promoter. At birth, Tg(Nphs1-Nog) mice, which had loss of BMP4 function in podocytes, were found to have glomerular microaneurysms, collapsed glomerular capillary tufts, enlarged Bowman's capsules, and fewer normal proximal tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 21 publications
2
35
0
Order By: Relevance
“…An elegant series of mutants that varied Vegfa protein production in podocytes highlights the critical role of Vegfa signaling in forming the capillary bed (Eremina et al 2003(Eremina et al , 2007. Glomerular formation is also regulated by Bmp4 in podocytes, and PdgfB/Pdgfrb pathway controls mesangial cell recruitment (Lindahl et al 1998;Ueda et al 2008). The intricate specialization and polarization of podocytes, essential to the elaboration of slit diaphragms, is multifactorial and highly complex.…”
Section: Patterning Segmentation and Specialization Of The Epithelimentioning
confidence: 99%
“…An elegant series of mutants that varied Vegfa protein production in podocytes highlights the critical role of Vegfa signaling in forming the capillary bed (Eremina et al 2003(Eremina et al , 2007. Glomerular formation is also regulated by Bmp4 in podocytes, and PdgfB/Pdgfrb pathway controls mesangial cell recruitment (Lindahl et al 1998;Ueda et al 2008). The intricate specialization and polarization of podocytes, essential to the elaboration of slit diaphragms, is multifactorial and highly complex.…”
Section: Patterning Segmentation and Specialization Of The Epithelimentioning
confidence: 99%
“…27 Considering that the renal TGF-b production is provoked by Aldo effects, 27 BMPs may have an antagonistic role in Aldo-induced TGF-b actions leading to amelioration of glomerular sclerosis. Recently, Ueda et al 28 reported that BMP-4 dysfunction in developing podocytes leads to abnormal formation of glomerular capillary tuft. In that study, a BMP-binding protein, noggin-overexpressing mice in podocytes developed glomerular microaneurysms and collapse of glomerular capillary tufts.…”
Section: Bmp-4mentioning
confidence: 99%
“…These data suggest that podocyte-derived BMPs have an important role in glomerular capillary formation in a paracrine manner. 28 Given that BMPs act to suppress mesangial cell proliferation in vitro, 15 it is possible that the BMP system in the renal cortex has a role in antagonizing renal injury induced by Aldo and high-salt treatment. We previously reported that Aldo stimulated thymidine incorporation of mesangial cells in a concentration-dependent manner in vitro via MR actions.…”
Section: Bmp-4mentioning
confidence: 99%
“…49 In addition, blockade of BMP4 function in the transgenic Nephrin-Noggin mice with podocyte-selective expression of BMP inhibitor Noggin caused enlargement of glomerular capillaries or microaneurysms and dilated Bowman's capsules with collapsed glomerular capillary tufts, which were similar to those capillaries and capsules observed in Bmp4 +/2 mice. 50 Nephrin-Noggin mice also showed a decrease in the number of mesangial cells in the glomeruli. Similarly, in the Tak1 Δ/Δ kidney, a major morphologic change found was the enlargement of glomerular capillaries and abnormal capillary development.…”
Section: Discussionmentioning
confidence: 95%